Sharpening the Edge for Precision Cancer Immunotherapy: Targeting Tumor Antigens through Oncolytic Vaccines - Holay, Namit; Kim, Youra; Lee, Patrick; Gujar, Shashi (Frontiers in Immunology, 2017)
Cancer immunotherapy represents a promising, modern-age option for treatment of cancers. Among the many immunotherapies being developed, oncolytic viruses (OVs) are slowly moving to the forefront of potential clinical therapeutic agents, especially considering the fact that the first oncolytic virus was recently approved by the FDA for the treatment of melanoma. OVs were originally discovered for their ability to kill cancer cells but they have emerged as unconventional cancer immunotherapeutics due to their ability to activate a long-term, anti-tumor immune response. This immune response not only eliminates cancer cells but also offers potential for preventing cancer recurrence. A fundamental requirement for the generation of such a strong anti-tumor T cell response is the recognition of an immunogenic tumor antigen by the anti-tumor T cell. Several tumor antigens capable of activating these anti-tumor T cells have been identified and are now being expressed through genetically engineered OVs to potentiate anti-tumor immunity. With the emergence of novel technologies for identifying tumor antigens and immunogenic epitopes in a myriad of cancers, design of “oncolytic vaccines” expressing highly specific tumor antigens provides a great strategy for targeting tumors. Here, we highlight the various oncolytic viruses engineered to target tumor antigens, and discuss multiple studies and strategies used to develop oncolytic vaccine regimens. We also contend how, going forward, a combination of technologies for identifying novel immunogenic tumor antigens and rational design of oncolytic vaccines will pave the way for the next generation of clinically efficacious cancer immunotherapies.